Aerobic Exercise Intervention to Increase VO₂ Max Capacity of Higher Students in College Environment - Nurulita, Retno Farhana; Yusnadi, Yusnadi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Low physical activity among higher students impacts those with less than optimal cardiorespiratory capacity. One important indicator of physical fitness is VO₂ max. This study aims to evaluate the impact of aerobic exercise on higher students. The research method used a quasi-experimental design with a pre-test and post-test approach without a control group. The subjects of the study were 96 students from the Faculty of Sport Science and the Faculty of Public Health, Makassar State University, aged 19–22 years, who participated in an aerobic exercise program for eight weeks with a frequency of four times a week and a duration of 60 minutes per session. VO₂ max measurements were carried out using the Modified Cooper Test. The findings of the analysis revealed that the average VO₂ max increased from 32.1 ml/kg/minute to 38.7 ml/kg/minute (p < 0.001), representing a 20.5% increase. This study proves that aerobic exercise is an effective and applicable form of intervention to improve the cardiorespiratory fitness of higher students. Aerobic exercise programs should be incorporated into the campus health agenda to promote a sustainable, active, and healthy lifestyle.